THE “ISLAMIC REVIVAL” IN DAGHESTAN TWENTY YEARS LATER - BOBROVNIKOV, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2007)
The Caucasian Muslims witnessed a tempes tuous Islamic upswing during the last decade of the 20th century and at the beginning of the new millennium. As though by the wave of a magic wand, the region was transformed from Soviet into Islamic. The outer appearance of towns and villages drastically changed, along with the very tempo of private and public life. Islam became the basis on which children and adolescents socialized. Islamic schools and higher education institutions opened. Islamic parties and movements of different trends, Islamic periodicals, and even a Russian-language Islamic Internet appeared. Sufi sheikhs emerged from the underground. In the East-ern Caucasus, the Naqshbandi, Shazili, and Qadiri orders are functioning openly again. Islam has be-come a marketable political trump card, and every politician is rushing to assure the Muslim how much he loves and wants to protect him. The statements of Daghestan President Mukhu Aliev are typical in this respect: “We have no history without religion, and we will help our traditional religious trends and strengthen the position of the Spiritual Admin-istration of Muslims with this goal in mind…”1 Daghestan found itself in the epicenter of the move-ment. Reislamization has assumed more vehement and at times grotesque forms here. It will soon be twenty years since the Islam-ic upswing or revival, as the people in Daghestan like to call it, began. Perestroika set it in motion. It is worth doing some tallying up on the eve of this “glorious anniversary.” Particularly since, after all the upheavals of the post-perestroika period, it appears that life both in Russia and the Caucasus has calmed down somewhat. It is time to think about the lessons that can be learned from the Islamic boom in Daghestan. As an ethnographer, I would like to do this by turning to the information gathered in the republic between the fall of 1992 and the winter of 2006.2 I was lucky enough to witness both the beginning of the Islamic boom and the slump in the fervor over Islam that began at some point after the mid-2000s. Returning to the problem of the post-Soviet forms of Islam, which I have written about repeatedly, including in Central Asia and the Caucasus, I would like to clarify several still not entirely clear questions about the nature and consequences of the Islamic boom.hat caused the Islamic revival? How does it correlate with the Soviet imperial past in the Caucasus? What has the Islamic boom done for Daghestan? What ended up being revived, and has any-thing actually been revived? And, finally, is there a correlation between the revival of Islam and the increase in conflicts and instability in the region?